2010
DOI: 10.3340/jkns.2010.48.5.452
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Atlantoaxial Rotatory Fixation with Accompanying Odontoid and C2 Articular Facet Fracture

Abstract: J Korean Neurosurg Soc 48 : [452][453][454] 2010 Traumatic atlantoaxial rotatory fixation (AARF) with accompanying odontoid and C2 articular facet fracture is a very rare injury, and only one such case has been reported in the medical literature. We present here a case of a traumatic AARF associated with an odontoid and comminuted C2 articular facet fracture, and this was treated with skull traction and halo-vest immobilization for 3 months. After removal of the halo-vest immobilization, his neck pain was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…AARF can also be associated with fractures, due to a combination of bone and ligament disruption but this association is very rare; C2 fractures are relatively the most frequently founded, and only six such cases have been reported in the literature[ 8 9 ]; but AARF in combination with an articular facet fracture, like in our case, is an extremely rare injury and to the best of our knowledge only Seybold described similar case. [ 10 ] However, because of the complexity and heterogeneity of these fractures, they are usually lumped under the descriptive category of “miscellaneous C2 fractures” in most published reports.…”
Section: Discussionmentioning
confidence: 69%
“…AARF can also be associated with fractures, due to a combination of bone and ligament disruption but this association is very rare; C2 fractures are relatively the most frequently founded, and only six such cases have been reported in the literature[ 8 9 ]; but AARF in combination with an articular facet fracture, like in our case, is an extremely rare injury and to the best of our knowledge only Seybold described similar case. [ 10 ] However, because of the complexity and heterogeneity of these fractures, they are usually lumped under the descriptive category of “miscellaneous C2 fractures” in most published reports.…”
Section: Discussionmentioning
confidence: 69%
“…Traumatic C1-C2 dislocation complicating an odontoid fracture is relatively rare, and most of these cases are probably fatal (Pissonnier et al 2013 ). Some previous reports showed that reduction and fixation could be achieved by halo vest, resulting in successful healing of the dislocation and fracture (Spoor et al 2008 ; Oh et al 2010 ). However, similar to the present case, in most of the cases described in the literature, the use of a halo vest alone failed to reduce the dislocation, and therefore surgical fixation was performed secondarily (Lenehan et al 2010 ; Hopf et al 2009 ; Moreau et al 2012 ; Przybylski & Welch 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Until the beginning of this century, C1-C2 dislocations with associated odontoid fractures had been described by 11 authors [8, 1019] . Two cases were managed by halo-vest immobilization for 3–4 months [18, 19], another case was treated by anterior C1-C2 fixation according to Vaccaro’s technique [13], and all other cases were treated by C1-C2 posterior fixation [8, 1012, 1417]. One important pitfall of closed reduction techniques is overdistraction [20].…”
Section: Discussionmentioning
confidence: 99%